PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KETERAMPILAN PROSES SAINS PESERTA DIDIK KELAS X SMA NEGERI 3 BONE - Arafah, Kaharuddin; Haris, Abdul; Arsyad, Azhar (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2025)
Physics is a branch of science that plays an important role in students' science process skills. One learning model that focuses on science process skills is the Discovery Learning model. This research aims to determine the improvement in students' science process skills before and after the Discovery Learning model was implemented in class X SMA Negeri 3 Bone. The research method used was a pre-experimental study with a One Group Pretest-Posttest design. The first stage involved administering a pretest to measure initial abilities, the second stage involved implementing the Discovery Learning model, and the third stage involved administering a posttest to measure science process skills and evaluate the learning that had taken place. The sample in this research consisted of 33 students in class X EI of SMA Negeri 3 Bone in the 2024/2025 academic year. Science process skills were measured using a test instrument based on the indicators of questioning and predicting, classifying, planning investigations, applying concepts, analyzing data and information, evaluating, and communicating. Based on the results of descriptive statistical analysis, the average pretest and posttest scores were 10.38 and 15.26, respectively. Meanwhile, the results of the N-Gain analysis showed an average of 0.80, which is classified as high. Thus, it can be concluded that the application of the Discovery Learning model can significantly improve the science process skills of grade X EI students at SMA Negeri 3 Bone in the high category.